Governor Partisanship Explains the Adoption of Statewide Mask Mandates in Response to COVID-19. Issue 1 (20th March 2022) - Adolph, Christopher; Amano, Kenya; Bang-Jensen, Bree; Fullman, Nancy; Magistro, Beatrice; Reinke, Grace; Wilkerson, John
Abstract: Public mask use has emerged as a key tool in response to COVID-19. We develop a classification of statewide mask mandates that reveals variation in their scope and timing. Some US states quickly mandated wearing of face coverings in most public spaces, whereas others issued narrow mandates or no mandate at all. We consider how differences in COVID-19 epidemiological indicators and partisan politics affect when states adopted broad mask mandates, starting with the earliest mandates in April 2020 and continuing through the end of 2020. The most important predictor is the presence of a Republican governor, delaying statewide indoor mask mandates an estimated 98.0 days on average. COVID-19 indicators such as confirmed case or death rates are much less important predictors. This finding highlights a key challenge to public efforts to increase mask wearing, one of the most effective tools for preventing the spread of SARS-CoV-2 while restoring economic activity.